Management of an Intraparenchymal Struvite Stone Using Laparoscopic Nephrolithotomy: A Case Report - Ayoub Hidayat‐Allah; Frank Friedersdorff (Clinical Case Reports)
ABSTRACT This study aims to present a case of laparoscopic nephrolithotomy and highlight its successful outcome. The patient was a 65‐year‐old male who experienced intermittent colicky flank pain. Imaging revealed the presence of a 20‐mm round‐shaped stone in a hydronephrotic calyx located in the mid‐pole of the left kidney, possibly with a parenchymal component. Given the stone's location, neither percutaneous nephrolithotripsy (PCNL) nor ureterorenoscopy (URS) was considered feasible. The findings of this study demonstrate the effectiveness and suitability of laparoscopic nephrolithotomy (LNL) in managing stones. It emphasizes that LNL can be utilized not only as an alternative treatment but also as a viable initial option when appropriate case selection is made.